2010
DOI: 10.1002/ldr.1064
|View full text |Cite
|
Sign up to set email alerts
|

Seeding and mulching + seeding effects on post‐fire runoff, soil erosion and species diversity in Galicia (NW Spain)

Abstract: The effects of two different soil rehabilitation treatments on runoff, infiltration, erosion and species diversity were evaluated in a shrubland area in Galicia (NW Spain) after an experimental fire by means of rainfall simulations. The treatments compared were: seeding, seeding + mulching and control (untreated). Rainfall simulations were conducted 9 months after fire and the application of soil rehabilitation treatments. A rainfall rate of 67 mm h−1 was applied for 30 min to each runoff plot. Seeding signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 35 publications
4
47
1
2
Order By: Relevance
“…Therefore, there is a need to find a balance between the cost and the efficiency of the straw mulch cover. In this regard, there are other researchers who studied the efficiency of mulches on fire affected land and found that the mulch cover of mulches does not need to be high to be efficient (Fernández et al, 2012;Prats et al, 2014;Robichaud et al, 2013a;2013b). In these cases, straw mulch was confirmed to have a positive effect on water quality (Faucette et al, 2007) and the mitigation of wind-induced soil erosion (Nelson, 2002).…”
Section: Tablementioning
confidence: 97%
“…Therefore, there is a need to find a balance between the cost and the efficiency of the straw mulch cover. In this regard, there are other researchers who studied the efficiency of mulches on fire affected land and found that the mulch cover of mulches does not need to be high to be efficient (Fernández et al, 2012;Prats et al, 2014;Robichaud et al, 2013a;2013b). In these cases, straw mulch was confirmed to have a positive effect on water quality (Faucette et al, 2007) and the mitigation of wind-induced soil erosion (Nelson, 2002).…”
Section: Tablementioning
confidence: 97%
“…Planting and seedling methods for installing vegetation on slopes are therefore required. Such methods have already been tested on several other eroded lands (Reubens et al, 2009;Bochet et al, 2010;Fernández et al, 2012;Commander et al, 2013;Lee et al, 2013), but these studies did not apply to our climatic, topographic and pedological conditions, and the studied plant species are not appropriate or currently available. Therefore, the main issue for practitioners is to find the adequate solution to develop vegetation cover on gully slopes.…”
Section: Breton Et Al: Effects Of Wood Chip Amendments On the Revmentioning
confidence: 99%
“…Therefore, post-fire soil stabilisation techniques (e.g. seeding and mulching) must be applied as soon as possible to accelerate development of ground and vegetation cover, reduce surface runoff and prevent soil erosion (Pinaya et al 2000;Robichaud et al 2000;Vega et al 2005;Wagenbrenner et al 2006;Robichaud 2009;Fernandez et al 2011Fernandez et al , 2012. In many countries, seeding of fast-growing non-native grass species is the most common post-fire stabilisation technique to rapidly increase plant cover because of its relatively low cost and easy aircraft application (Robichaud et al 2000;Beyers 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, this practice has been questioned because it can introduce exotic species (Kruse et al 2004) and displace native species, interfering with natural vegetation recovery (Beyers 2004). Furthermore, grass seeding could be ineffective in increasing ground cover or reducing erosion rates during the first critical rain events after a fire (Robichaud et al 2006;Wagenbrenner et al 2006;Groen and Woods 2008;Peppin et al 2010;Fernandez et al 2012). As an alternative, straw mulch is increasingly being applied to burnt areas with high value due to its immediate effectiveness in increasing ground cover and erosion control (Bautista et al 2009;Robichaud et al 2010).…”
Section: Introductionmentioning
confidence: 99%